RNA-seq Profiling Reveals Novel Target Genes of LexA in the Cyanobacterium Synechocystis sp. PCC 6803 - Kizawa, Ayumi; Kawahara, Akihito; Takimura, Yasushi; Nishiyama, Yoshitaka; Hihara, Yukako (Frontiers in Microbiology, 2016)
LexA is a well-established transcriptional repressor of SOS genes induced by DNA damage in E. coli and other bacterial species. However, LexA in the cyanobacterium Synechocystis sp. PCC 6803 has been suggested not to be involved in SOS response. In this study, we performed RNA-seq analysis of the wild-type strain and the lexA-disrupted mutant to obtain the comprehensive view of LexA-regulated genes in Synechocystis. Disruption of lexA positively or negatively affected expression of genes related to various cellular functions such as phototactic motility, accumulation of the major compatible solute glucosylglycerol and subunits of bidirectional hydrogenase, photosystem I and phycobilisome complexes. We also observed increase in the expression level of genes related to iron and manganese uptake in the mutant at the later stage of cultivation. However, none of the genes related to DNA metabolism were affected by disruption of lexA. DNA gel mobility shift assay using the recombinant LexA protein suggested that LexA binds to the upstream region of pilA7, pilA9, ggpS and slr1670 to directly regulate their expression, but changes in the expression level of photosystem I genes by disruption of lexA is likely a secondary effect.